INFLUENCE OF STAGES OF FULL LIFE CYCLE ON SAFETY OF COMPLEX TECHNICAL SYSTEMS - M. V. Volkov; A. A. Yaroslavtseva (Научный вестник МГТУ ГА)
The article deals with the stages of the life cycle, according to regulatory guidance documents and their impact on the safety of complex technical systems. The planning and management system shortcomings of the complex technical systems development are highlighted.